Taboo in Balinese Language Spoken in Puri Tukadmungga - Agita, Anak Agung Ayu Ngurah (Journal of Linguistic and Literature Studies, 2023)
This study explores the use of taboo language in the Balinese language spoken in Puri Tukadmungga, focusing on the identification and categorization of taboo words across different domains. The study successfully identifies 23 taboo words within the "pawongan" domain, associated with human-to-human relationships, and two taboo words within the "palemhan" domain, linked to human-environment relationships. The significance of triangulating theories and analytical models, particularly the interactive model adapted from Miles Huberman, is underscored, providing a profound understanding of the findings. The study proposes directions for future research, including exploring taboo words in other domains, examining social and cultural implications, and utilizing larger sample sizes and diverse theoretical perspectives. Overall, this paper offers in-depth interview into taboo language in the Balinese language at Puri Tukadmungga, differentiating taboo words across various domains, and emphasizes the importance of triangulating theories and analytical models. Recommendations for further research are presented to enhance understanding in this field.